Effect of Enterprise Multiple on Stock Return Non-Financial Companies in Indonesian Stock Exchange - Namira, Fitri; Nugroho, Bernardus Yuliarto (UI Scholars Hub, 2018)
Enterprise Multiple is widely used by practitioners as a valuation measure (Loughran & Wellman, 2011). Furthermore, one component used in the calculation of enterprise multiple (EV/EBITDA) is the use of operating income before depreciation data as income variables. The data is accurate and difficult to manipulate (not even) in measuring the profitability of a company over net income. This study aims to analyse the influence of enterprise multiple on stock return towards non-financial companies listed in the Indonesian Stock Exchange from 2006-2015. The dependent variable used is stock return. The independent variable used is enterprise multiple which is proxied with EV / EBITDA. Enterprise Value (EV) is (value of equity + debt + preferred stock - cash). While EBITDA are Earnings Before Interest, Tax, Depreciation and Amortisation. This research takes the form of a quantitative research by using panel data regression test. The results show that firms with a low enterprise multiple values, have a higher stock return than firms with high enterprise multiple values. In addition, the portfolio established under enterprise multiple values (low minus high portfolios) in the Carhart 4 Factor Model is robust on non-financial companies listed on the Indonesia Stock Exchange 2006-2015 period.